Artificial Nails and Long-lasting Nail Polish in Danish Hairdressers: Self-use, Occupational Exposure and Related Eczema - Martin Havmose; Jacob P. Thyssen; Claus Zachariae; Jeanne D. Johansen (Medical Journals Sweden, 2022)
Artificial nail modelling systems (ANMS), encompassing artificial nails and long-lasting nail polish, are sources of acrylate exposure in beauticians and users of ANMS. Hairdressers' exposure to ANMS from self-use and occupational exposure is currently unknown. In 2020 a questionnaire was sent to all hairdressers graduating during 2008 to 2018 in Denmark (n = 4,830). Self-use of ANMS was reported by 87.6% of respondents (1,251/1,428), and application of ANMS to others was reported by 22.1% (316/1,428). Of these, application to others was performed in a salon by 37.1% (109/294), privately by 51.0% (150/294) and in both settings by 11.9% (35/294). Compliance with glove use was seen in 23.0% (67/291) among those applying ANMS to others. Among hairdressers exposed to ANMS, 4.3% (52/1,218) reported ANMS-related hand eczema. Being a trained beautician (adjusted odds ratio 3.26, 95% confidence interval 1.06-9.99) and having had a positive patch-test to acrylates (adjusted odds ratio 7.70, 95% confidence interval 1.44-41.13) were associated with ANMS-related hand dermatitis. In conclusion, hairdressers have a high prevalence of exposure to ANMS and ANMS-related hand dermatitis. Compliance with glove use when applying ANMS to others is poor. Patch-testing with acrylates is valuable in the diagnostic work-up of hand eczema in hairdressers.